Chickenpox: An update - Leung, Alexander K.C.; Kellner, James D.; Davies, H. Dele (Journal of Pediatric Infectious Diseases, 2009)
Chickenpox, caused by the varicella-zoster virus, is mostly a mild disease in healthy children, but can be debilitating in immunocompromised individuals or susceptible adults. The disease is highly contagious. The lesions start as rose-colored macules, and progress rapidly to become papules, vesicles with the classic “dew drop on a rose petal” appearance, pustules and, finally, crusts. The distribution of the lesions is typically central, with the greatest concentrations on the trunk. Characteristically, lesions are intensely pruritic and appear in crops. The most common complication associated with chickenpox is secondary bacterial infections of the skin followed by post-inflammatory scarring of the lesions. The diagnosis is mainly clinical and treatment symptomatic. Oral acyclovir should be considered in high-risk individuals. Intravenous acyclovir is effective for the treatment of chickenpox in immunocompromised individuals and for serious complications of chickenpox in normal patients. To eradicate chickenpox, universal childhood immunization with varicella vaccine is the way to go. The Advisory Committee for Immunization Practices of the Centers for Disease Control and Prevention and the American Academy of Pediatrics recommend a routine two-dose varicella vaccination program for children, with the first dose administered at 12 to 18 months and the second dose at 4 to 6 years of age. The Advisory Committee on Immunization Practices further recommends two doses of varicella vaccine, 4 to 8 weeks apart, for all susceptible adolescents and adults and a catch-up second dose for everyone who received one dose of varicella vaccine previously.
Keywords: Chickenpox; complications; universal immunization; two doses